A wind in the door - L'Engle, Madeleine (New York : Square Fish, 2007)
With Meg Murry's help, the dragons her six-year-old brother saw in the vegetable garden play an important part in his struggle between life and death.
Sequel to: A wrinkle in time.
Keywords: Science fiction